Kaedah-Kaedah Jarh Dan Ta’dil Dalam Penelitian Hadis Nabi - Muhammad Tohir Ritonga (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2023)
The Hadith is the second source of Islamic law after the Koran which serves as a bayan for verses of the Qur'an. As the main source of Islamic teachings, it should require research and standard methods in determining the quality of a hadith. then in this study will be described the rules of al-Jarh wa Ta'dil to establish the assessment status of a periwayat. This study uses a descriptive qualitative method and aims to clearly outline every rule of thumb related to jarh wa ta'dil. This Study’s results the rules of jarh wa ta'dil are systematically deciphered and concluded into the main rules of Jarh wa Ta'dil science.